Disease prevalence and symptoms caused by Alternaria tenuissima and Pestalotiopsis guepinii on blueberry in Entre Ríos and Buenos Aires, Argentina - Fernández, Rocío L. (2015)
About 60% of blueberry (Vaccinium corymbosum) plantations in Argentina are located in the provinces of Entre Ríos and Buenos Aires. Alternaria tenuissima and Pestalotiopsis guepinii have been reported as pathogens of blueberry, causing leaf spots and branch cankers. The aims of this research were to estimate the prevalence of these microorganisms on leaves and fruits taken from crops located in Entre Ríos and Buenos Aires, as well as to differentiate leaf symptoms after target inoculations with each pathogen individually and in mixtures. Both fungi were present in blueberry fields from 2010 to 2013. A. tenuissima was the most prevalent pathogen, as most of the symptoms detected in the fields had been caused by this species. As a result of inoculations on cv. O’Neal, injured tissues showed symptoms before undamaged ones. Leaf symptoms caused by A. tenuissima differed from those caused by P. guepinii because of their predominant reddish color and the absence of drop-off of the central part of the lesions. When inoculated in a mixture, incubation period on leaves was intermediate between the registered for individual inoculations. The leaves showed reddishbrown spots typical of A. tenuissima and dark brown spots typical of P. guepinii, both with red margins. Blight, defoliation and canker symptoms caused in each case were undistinguishable.